„Nec temere neque iniuste, sed consulto et aequitatis ductu in hanc terram transvectus sum” (GG II, 12) – The Legitimisation of the Rule in William of Poitiers’ Gesta Guillelmi - Dźwigała, Bartłomiej (Saeculum Christianum. Pismo Historyczne, 2021)
The aim of the article is to analyse first medieval biography of William the Conqueror in order to explain the issue of legitimisation of the Norman rule in England. In the introduction I present the author of Gesta Guillelmi and his work. The main part of the article contains detailed explanatory narrative’s elements used by the author to provide ideological justifications for William the Conqueror’s rule in London.